Staff Perceptions on Workplace Comfort and Working Postures within the Context of Office Ergonomics in an Information Technology Firm - Zakaria, Nurihan; Jamian, Rahim; Ismail, Elya Atikah (Progress in Engineering Application and Technology, 2025)
Office ergonomics refers to an office setting that relates to items including chairs, desks, computers, and other elements that comprise an employee’s workstation. Discomfort and injuries known as work-related musculoskeletal disorders (WMSD) are common issues among office staff due to poor office ergonomics. Office ergonomics issues can affect the productivity and work efficiency in various industries and business sectors. This study analysed the perception of staff on the workplace comfort and working posture within the context of office ergonomics in an information technology (IT) firm. A questionnaire survey comprising of multiple section were used to collect the perception of staff on their office furniture provided and their working postures. In the survey, 51 (n) of 56 (N) staff members from selected departments of an IT company provided responses. The survey comprised three sections: staff perspectives on the working environment, nature of work, and its impact; a self-assessment of posture; and open-ended suggestions for workstation improvements. Results showed high comfort levels for the work environment, moderate comfort for job nature and conditions, and moderate influence of the work environment on staff. While most practiced proper posture, some were at risk for ergonomic issues due to poor practices. The majority agreed on the need for workstation improvements. As a result, it could be seen that the degree of comfort among office staff in the company is modest, and majority of staff are satisfied with the workstation and office chair that are provided by the organization.